Pengabdian Masyarakat Desa Purworejo UMKM Naik Kelas: Legal, Digital, Gobal, Financial - Amah, Nik; Aviyanti, Richo Diana; Sudrajat, M. Agus; Novitasari, Maya; Adiputra, Eka; Permatasani, Arsinta Ayu (Universitas PGRI Madiun, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the local economy, but still face various challenges, particularly related to business legality, digitalization, marketing, and financial management. This community service activity aims to increase the capacity of MSMEs in Purworejo Village, Madiun Regency, through assistance related to business legality, financial intelligence, MSME digitalization, and digital marketing strategies. The activity implementation methods included counseling, training, discussions, and mentoring for 11 MSMEs. The results of the activity showed that 55% of participants have implemented simple financial records, 36.4% have begun utilizing digital strategies and social media for product marketing, and 27.3% demonstrated readiness in managing business legality. These findings indicate that the activity was able to increase the understanding and awareness of MSMEs, although the level of practical implementation still requires further mentoring for the results of the activity to be sustainable. This activity is expected to become a model for MSME empowerment based on integrated capacity building to encourage MSMEs to move up a class.